Private academies of Tokugawa Japan - Rubinger, Richard, 1943- (Princeton legacy library., 1982)
Widening the focus of previous studies of Japanese education during the Tokugawa period, Richard Rubinger emphasizes the role of the shijuku, or private academies of advanced studies, in preparing Japan for its modern transformation.Originally published in 1982.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.